2022
DOI: 10.1155/2022/8109977
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Seroconversion Remains High among Patients with Regular Hemodialysis: Study of Associated Risk Factors

Abstract: Background/Aims. Hemodialysis patients have a higher risk of hepatitis C compared to the general population. The burden of hepatitis C infection among hemodialysis patients is substantial and was estimated to rise constantly. This study is aimed at determining the frequency of HCV seroconversion and associated risk factors among hemodialysis patients in our unit. Methods. An analytical cross-sectional study involving patients from 2 dialysis units (1 referral hospital and 1 private dialysis unit) in Denpasar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…The logistic regression analysis further substantiated the finding that patients with a permanent central venous catheter exhibited a higher likelihood of testing positive for HEV compared to patients with an AV fistula (OR = 12.26, 95% CI: 2.19-68.73). We did not find such an association in the available literature, but one has been reported for vascular access and HCV seroconversion in hemodialysis patients [52], indirectly pointing to a parenteral route of virus transmission. It is likely that vascular access in dialysis patients would be important for the nosocomial transmission of HEV, based also on the fact that low-molecular-weight heparins, used to maintain vascular patency and prevent thrombotic complications, are extracted from the porcine small intestine [53].…”
Section: Discussioncontrasting
confidence: 60%
“…The logistic regression analysis further substantiated the finding that patients with a permanent central venous catheter exhibited a higher likelihood of testing positive for HEV compared to patients with an AV fistula (OR = 12.26, 95% CI: 2.19-68.73). We did not find such an association in the available literature, but one has been reported for vascular access and HCV seroconversion in hemodialysis patients [52], indirectly pointing to a parenteral route of virus transmission. It is likely that vascular access in dialysis patients would be important for the nosocomial transmission of HEV, based also on the fact that low-molecular-weight heparins, used to maintain vascular patency and prevent thrombotic complications, are extracted from the porcine small intestine [53].…”
Section: Discussioncontrasting
confidence: 60%
“…Numerous factors including duration of HD, attending multiple centers for HD, a history of invasive procedures, type of vascular access, dialyzer reuse, and frequency of blood transfusion were observed to be associated with HCV seroconversion 1,2,[22][23][24] . In the study by Dharmesti et al, HCV seroconversion was found in 28% of the patients who were on regular dialysis, HCV seroconversion was significantly associated with vascular access type (OR=42.1, 95% CI=5.8 to 307.4) and dialyzer reuse (OR=8.3, 95% CI=4.32-16.04) 6 ., Mahupe et al in their study found that HD duration, no. of hospital admissions, history of invasive procedures, and blood transfusions were not associated with seropositivity of HCV 25 .…”
Section: Discussionmentioning
confidence: 95%
“…Despite all these measures, HCV prevalence in the hemodialysis unit is still higher than in the general population, which is less than 1% for blood donors [ 13 ]. This is because these patients are at high risk of infection as a result of a number of factors, including the frequent and prolonged potential exposure to blood, the close distance of dialysis patients to each other, health care staff moving between patients, frequent hospitalization and surgery, and more importantly, non-adherence of health care workers to the recommended infection control practices [ 5 , 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the As Seeb Dialysis Center has higher seroprevalence than the Bawshar Dialysis Center (13.9% and 5.7%, respectively), which can be explained by the fact that it is a dedicated unit for the known infected cases as they have more isolation rooms. Nevertheless, more attention is needed for evaluation of infection prevention and control practices, including the failure to adhere to good hand hygiene and the proper use of gloves which both were described in different studies as a cause for outbreaks in dialysis units [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation